PENGEMBANGAN MODUL IPA TERPADU BERBASIS SAINS-LINGKUNGAN-TEKNOLOGI-MASYARAKAT (SALINGTEMAS) DENGAN TEMA TEKNOLOGI BIOGAS - Sugiyanto Sugiyanto; Ika Kartika; Joko Purwanto (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
This study aims to develop the module based Integrated science environment technology society (SETS), knowing the quality of modules according to matter experts, media specialists and science teachers SMP / MTs, as well as the response of students to the module. Integrated Science is the study or the development of Research and Development (R & D) procedural models, the model is descriptive, showing the steps to be followed to produce the product. The procedure follows the development of Borg and Gall procedures that can be done more simply by involving five major steps: 1) to analyze the product to be developed; 2) develop the initial product, 3) validation of the expert and revision, 4) small-scale field trials and revision of the product; 5) large- scale field trials and the final product. The results of the module-based Integrated Science (SETS) with the theme of biogas technology. Based on an assessment matter experts, media specialists and science teachers SMP/MTs module Integrated IPA has developed a very good quality with score of 87.69 of the ideal of matter experts, 76.78 of the ideal score of media expert, and 77.75 of the ideal score of teacher SMP/MTs. As for the students' responses on a small scale field trials and large-scale field trials get very good response with score of 78.75 of the ideal in small-scale field trials and 81.17 of the ideal score on a scale field trials great.